ANALISIS CATCH PER UNIT EFFORT (CPUE) DAN MAXIMMUM SUSTAINABLE YIELD (MSY) IKAN CAKALANG (KATSUWONUS PELAMIS) YANG DIDARATKAN DI PELABUHAN PERIKANAN SAMUDERA (PPS) KENDARI - febriyani palungan; Andi Irwan Nur; Romy Ketjulan (Universitas Mataram, 2024)
Skipjack tuna is one of the large pelagic fish landed at the Kendari Ocean Fisheries Port (PPS Kendari). The objective of this research is to analyze the Catch per Unit Effort (CPUE) and Maximum Sustainable Yield (MSY) of skipjack tuna (Katsuwonus pelamis) landed at PPS Kendari. The study was conducted in November-December 2023 at PPS Kendari. Data obtained from PPS Kendari for the years 2016-2022 include the catch of landed skipjack tuna, types of fishing gear used, and the quantity of catch for each type of gear. The research method employed is the surplus production Scheafer method. Fishing gear used to catch skipjack tuna landed at PPS Kendari includes gillnets, hand lines, pole and line, purse seines, boat seine, lift net, and others. The standard fishing gear used is the pole and line. The analysis of CPUE values for landed skipjack tuna at PPS Kendari tends to fluctuate, with the highest CPUE occurring in 2020 at 3,670 kg/trip and the lowest CPUE occurring in 2018 at 1,578 kg/trip. Based on the MSY analysis, the optimal fishing effort is determined to be 2126 trips per year, with an optimal catch quantity of 6,130,516 kg per year. The utilization of skipjack tuna at PPS Kendari has not reached the level of overfishing. It can be concluded that the fishing effort for skipjack tuna has not exceeded the limits of sustainable stocks in the Banda Sea, allowing for an increase in fishing effort to achieve maximum results while still adhering to the calculated MSY limits.